MEDIA INFORMASI PERUMAHAN AMUNTAI RT.11 BERBASIS WEBSITE MENGGUNAKAN SUB DOMAIN KAMPUNG KITO - Efitra Efitra; Mutamassikin Mutamassikin; Budy Satria; Adinda Raudhatul Jannah (Politeknik Negeri Sriwijaya, 2020)
Perumahan Amuntai RT. 11 is one of the RT that are interested in owning and creating a website to meet the needs of local residents as information media. This website information media is initiated from the idea that an organization, whether small or large, certainly has an information system such as a website. Website-based information media is an important requirement today and can provide broader knowledge and be able to manage data well. The stages in designing and socializing a website are carried out starting from coordination, analysis of data needs, system design and coding and testing as well as launching by conducting direct training for users and managers. The information media for the Amuntai RT.11 housing website consists of several menu features such as RT profiles, mosque profiles, Services, RT Potentials and News. Information media based on the Amuntai RT.11 housing website can be accessed through amuntairt11.kampungkito.org.